Worm Infections (Soil-Transmitted Helminthiasis) in Elementary School Students - Nur, Nur Hamdani; Kartini, Kartini; Arda, Zul Adhayani (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Environmental sanitation factors and human behavior factors are factors that greatly influence the occurrence of worm disease. The high incidence of worms is caused by environmental factors or demographic conditions in an area and is also influenced by community behavior. This study aims to determine the factors associated with the incidence of worms in elementary school students in Manggala District, Makassar City. This type of research is observational analytic with a cross-sectional study design. The population in this study were elementary school children in grades IV, V, and VI who attended SD Komplek Inpres, SD Perumnas Antang II, Manggala District, Makassar City, with a total sample of 61 samples. Sampling used the Systematic Random Sampling technique. This research found that 29.5% of elementary school students were positively infected, where Ascaris lumbricoides and Tricuris trichiura were the main infections. The results of the analysis showed that hand washing behavior (p=0.003), nail cleanliness (p=0.031), and clean water facilities (p=0.001) were significantly related to the incidence of worm infections in elementary school students, and the variable clean water facilities were the variable that most dominant in the incidence of worms in elementary school students.